The Brief Student–Teacher Classroom Interaction Observation: Using Dynamic Indicators of Behaviors in the Classroom to Predict Outcomes and Inform Practice. (December 2016) - Reinke, Wendy M.; Herman, Keith C.; Newcomer, Lori
Measures that can be used to identify malleable, dynamic indicators of teacher practices that lead to or are associated with student outcomes are needed to inform classroom interventions and consultation practices with teachers. The purpose of this study was to evaluate and validate the Brief Student–Teacher Classroom Interaction Observation in elementary classrooms (Grades K–3). A universal sample of 896 students was observed during classroom instruction. The measure was utilized to gather information on how teachers interacted with students with regard to their use of positive versus negative feedback during a 5-min window at the start of the school year. Findings indicate that students who received more negative feedback than positive feedback from their teacher were rated at the end of the year as having a significant increase in problems with emotion regulation, concentration problems, and observed disruptive behavior, whereas students who received more positive feedback demonstrated significant increases in prosocial behaviors. Implications for how this brief 5-min observation can be used to inform teacher practice and identify students at the start of the year in need of additional supports are discussed.